2009
DOI: 10.2320/matertrans.md200817
|View full text |Cite
|
Sign up to set email alerts
|

Brittle-Ductile Transition in Low Carbon Steel Deformed by the Accumulative Roll Bonding Process

Abstract: Brittle-ductile transition (BDT) behaviour was investigated in low carbon steel deformed by an accumulative roll-bonding (ARB) process. The temperature dependence of its fracture toughness was measured by conducting four-point bending tests at various temperatures and strain rates. The fracture toughness increased while the BDT temperature decreased in the specimens deformed by the ARB process. Arrhenius plots between the BDT temperatures and the strain rates indicated that the activation energy for the BDT di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Materials subjected to severe plastic deformation (SPD) show outstanding mechanical properties such as high strength and toughness [1][2][3][4][5][6][7], in contrast to coarse-grained materials. In addition, it has been reported that, in severally deformed Cu, the activation volume exhibits an inverse dependence on temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Materials subjected to severe plastic deformation (SPD) show outstanding mechanical properties such as high strength and toughness [1][2][3][4][5][6][7], in contrast to coarse-grained materials. In addition, it has been reported that, in severally deformed Cu, the activation volume exhibits an inverse dependence on temperature.…”
Section: Introductionmentioning
confidence: 99%
“…1820) For example, UFG copper with a large number of nano-twins shows the coexistence of high strength and high ductility 21,22) and UFG iron obtains the improved fracture toughness at low temperatures as compared to coarse-grained iron. 23,24) Therefore, UFG metals are strongly expected for new structural materials. However it is difficult to explain why these excellent mechanical properties breaking the trade-off relationship between strength and ductility (toughness) appear in UFG metals by using conventional theories or obtained elementary processes in atomistic simulations because the competition between the intragranular dislocation motion and grain-boundary-mediated plastic deformation processes could strongly influence the mechanical properties of UFG metals.…”
Section: Introductionmentioning
confidence: 99%
“…Arrhenius plots obtained from the deformation dependence of the BDT temperature. The activation energy for Fe-25Cr-1.1N was found to be 1.6 ± 0.9 eV, which is much higher than that for low carbon steel obtained in previous study 20) . 22) .…”
Section: 実験方法mentioning
confidence: 38%